Desnarrativas: workshop - Marques, Ivânia (Geografares, 2014)
This is a report of a teacher workshop. It was an encounter among dialogues, pictures and possibilities of deconstruction in multiple directions. It enables studies inspiring debate in favor of images. Images are loaded with clichés and they risk breaking with the documentary/real character of photography. It leads us to think of the non-neutrality of an image and how the place is hegemonically imposed on us. It does away with blocking forces in a playful experimentation. The experimentation is extended into compositions with photographs, monotype printing, and different ways of perceiving space, dialogues, exchanges, poems and art.Keywords: place; geographies; photographs.